Influence of Educational Methods on Bowel Preparation for Coloncopy: Systematic Literature Review - Kildušis, Edvinas; Brimas, Gintautas (Lietuvos chirurgija, 2021)
Background. To review and evaluate the influence of bowel preparation educational methods for colonoscopy used in world practice. Research material and methods. Scientific publications have been searched in PubMed, Cochrane Libraly, Google Scholar and SpringerLink databases since 2011 January 1 until 2020 May 10. The following keywords were used in the search: improving bowel preparation, cleansing, colonoscopy, education, enhanced, method, instruction, intervention, comparison, validated bowel preparation scale, adult participants. The specified inclusion and exclusion criteria were used in the selection of articles, and a detailed analysis of educational methods was performed. Results. This systematic review includes 21 articles, which assesses the various ways in which patients are educated before colonoscopy. The publications are divided into 3 groups: (1) patients in the study group educated in some way are compared with those in the control group who received standard instructions; (2) all patients received standard instructions, and the patients in the study group were additionally educated in some way and compared with the control group; (3) all patients received standard instructions, and patients in the study groups (there was more than one study group) were additionally educated in some way and the study groups were compared with each other. The main comparative results of the used bowel preparation for colonoscopy educational methods are presented. Conclusion. It is necessary to objectively (quantitatively, using standardized scales) evaluate the effectiveness of emerging patient bowel preparation before colonoscopy educational methods, to standardize patient training (education) protocols, so that it is possible to properly compare different forms of education.